2004
DOI: 10.1111/j.1398-9995.2004.00556.x
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of positive reactions in the atopy patch test with aeroallergens and food allergens in subjects with atopic eczema: a European multicenter study

Abstract: Aeroallergens and food allergens are able to elicit eczematous skin reactions after epicutaneous application. As no gold standard for aeroallergen provocation in AE exists, the relevance of aeroallergens for AE flares may be evaluated by APT in addition to SPT and sIgE. The data may contribute to the international standardization of the APT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
195
1
12

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 235 publications
(219 citation statements)
references
References 35 publications
11
195
1
12
Order By: Relevance
“…HDM was assumed to act not only as an allergen but also as a nonspecific irritant in AD skin lesions via a proteolytic activity of the HDM allergens. [25][26][27] In conclusion, this pilot study revealed that 24% of a group of allergic children from Cairo were sensitized to one or more of five strains of HDM, D. pteronyssinus and D. farinae being the most common. Testing children with several mite species would give information on the varied geographic distribution and might help efforts to develop more targeted specific immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…HDM was assumed to act not only as an allergen but also as a nonspecific irritant in AD skin lesions via a proteolytic activity of the HDM allergens. [25][26][27] In conclusion, this pilot study revealed that 24% of a group of allergic children from Cairo were sensitized to one or more of five strains of HDM, D. pteronyssinus and D. farinae being the most common. Testing children with several mite species would give information on the varied geographic distribution and might help efforts to develop more targeted specific immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in patients with food-triggered AD exacerbations, relevant food allergen-specific T cells have been detected in the peripheral blood as well as the skin (45,46). Moreover, positive atopy patch test (APT) reactions to inhalant and food allergens can be detected in the absence of corresponding IgE responses (47). Although widely used, the APT has limited value in the diagnosis of food allergy in EoE (16) perhaps owing to the fact that here the skin and not the esophagus is tested.…”
Section: Food-specific T-cell Responses In the Skinmentioning
confidence: 99%
“…In a European multicenter study, which included 314 patients with AEDS, the frequency of clear-cut positive APT reactions ranged from 39% with dust mites to 9% with celery. A notable observation from the study was that positive APT in face of all SPT and sIgE testing negative was found in 7% of the patients, whereas a positive APT without SPT or sIgE for the respective allergen was seen in 17% of the patients (42). This lead the authors to conclude that, as no gold standard for aeroallergen provocation in AEDS exists, the relevance of aeroallergens for AEDS may be evaluated by APT in addition to SPT and sIgE.…”
Section: The Allergy Tests In Diagnosis Of Aedsmentioning
confidence: 85%